THE EFFECT OF INTERNSHIP AND ENTREPRENEURSHIP TRAINING ON STRAT-UP PERFORMANCE WITH ENTREPRENEURIAL MOTIVATION AS AN INTERVENING VARIABEL - Puro, Intan Widia; Kussudyarsana; Nasir, Moechammad; Setyawan, Anton Agus (Jurnal Mebis, 2023)
This research aims to analyze the influence of internships and entrepreneurship training on start-up performance, both directly and through entrepreneurial motivation. This research used a quantitative approach with a sample of the first batch of UMS Independent Entrepreneurial Students in 2022, involving 869 participants. Sample selection criteria included full participation in the program and having an active business. The results of the analysis show that internships have a positive and significant impact on start-up performance and entrepreneurial motivation. While entrepreneurship training does not have a significant direct impact on start-up performance, it does influence entrepreneurial motivation significantly. Entrepreneurial motivation also has a significant positive impact on start-up performance. Interestingly, both internships and entrepreneurship training provide a significant positive impact on start-up performance when mediated by entrepreneurial motivation. Internships and entrepreneurship training have an important role in influencing start-up performance, especially when linked to entrepreneurial motivation. This emphasizes the importance of experience-based learning and formal training in supporting entrepreneurial spirit and performance among students in Indonesia.